Acute tonsillopharyngitis in a family practice in Mostar, Bosnia and Herzegovina - Budimir Mršić, Danijela (Array, 2009)
Abstract: The aim of this study was to examine the characteristics of acute tonsillopharyngitis diagnosis and treatment in the family care physicians in Mostar, Bosnia and Herzegovina. All patients diagnosed with acute tonsillopharyngitis in the Center of Family Medicine in Mostar in 2005 and 2006 were included in this study. Data were collected from medical records, including age and sex, month in which they visited their physician, symptoms and signs that they had (McIsaac’s clinical score was calculated accordingly) and treatment. Results showed that there were no gender differences regarding diagnosis. Mean age was 32.6 ± 16.9 years. The most patients were recorded during the January-March period. Total of 65.6% patients received antibiotic treatment. Phenoxymethylpenicillin, considered as the recommended antibiotic was used in 46.3% cases only. In conclusion, this first critical assessment of the existing family practice records on treating patients with tonsillopharyngitis suggested that physicians have to be more critical when treating patients with this diagnosis and that the knowledge and treatment of patients with pharyngitis need to be continuously improved in general medical practice